2017
DOI: 10.17660/actahortic.2017.1152.1
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic rainfall generator model for simulation of daily rainfall events in Kurau catchment: model testing

Abstract: Reservoirs play a substantial role in meeting water demands in arid and semi-arid regions especially with increasing changes in global rainfall patterns. Kurau catchment located at Northwest Perak, Malaysia, is the largest source of water to Bukit Merah Reservoir. Based on climate change effects on rainfall pattern, it is important to develop a model to simulate rainfall occurrence and amount that flow into the reservoir. To address this problem, a stochastic rainfall generator model based on first-order two-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…Table 1 shows a list of rainfall stations chosen for the study area. The data selected are within the study area due to the availability and suitability of the data for coupling with a stochastic rainfall generator [23]. The period of data used in this study is from 1976 to 2005 to validate rainfall from the CMIP6 model (historical period).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows a list of rainfall stations chosen for the study area. The data selected are within the study area due to the availability and suitability of the data for coupling with a stochastic rainfall generator [23]. The period of data used in this study is from 1976 to 2005 to validate rainfall from the CMIP6 model (historical period).…”
Section: Observationsmentioning
confidence: 99%
“…In comparison, Semenov and Barrow (1997) developed semi-parametric models that applied semi-empirical distributions to simulate rainfall processes. Details for further review on their history and previous successful application can be found from Wilby [22], Dlamini et al [8], Fadhil et al [23], and Liu et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…Model pembangkit curah hujan stokastik merupakan model stokastik yang menggunakan data meteorologi historis untuk membuat deret waktu harian berdasarkan parameter. Pembangkit curah hujan stokastik sering menggunakan pendekatan rantai Markov untuk menggambarkan kejadian curah hujan dan jumlah curah hujan dengan memasang fungsi distribusi untuk semua hari hujan (Fadhil, 2017).…”
Section: Aunclassified
“…Model pembangkit curah hujan stokastik menggunakan pendekatan rantai Markov untuk menggambarkan kejadian curah hujan dan untuk membangkitkan jumlah curah hujan dengan menggunakan fungsi distribusi (Fadhil, 2017). Pemodelan Kejadian Curah Hujan Kejadian curah hujan dimodelkan menggunakan pendekatan rantai Markov.…”
Section: B Metodologi Penelitian Model Pembangkit Curah Hujan Stokastikunclassified
“…KRB is located between 04 51′ N and 05 10′ N latitude and 100 38′ E to 101 01′ E longitude in Perak State of Malaysia, having an area of 322 km 2 and being the main drainage artery pouring into Bukit Merah Reservoir (BMR) (Fadhil et al, 2017). Analysis of rainfall-runoff processes in KRB is important because BMR is the key structure for rice production, flood control, ecosystems, and tourism in the region (Hamidon et al, 2015).…”
Section: Description Of Study Areamentioning
confidence: 99%